Eficacia jurídica de las medidas de protección dispuestas por la junta cantonal de protección de derechos del cantón Ibarra en el año 2018 - Brborich Garcia, Juan Andrés (2023)
The constitutional state of rights in which our country develops, recognizes the rights of children and adolescents under the help of the constitutionality block\; It also considers that there must be a National Decentralized System of Integral Protection for minors, this being a responsibility of the Municipal GADs at the national level to form Cantonal Boards for the protection of rights in each of its cantons. Thus, this paper is aimed at the diagnostic study on the legal effectiveness and application of the protection measures process that must be processed by the cantonal protection board of Ibarra as a viable mechanism for the protection of the rights of children. and adolescents who are considered as a priority care group as established by the Constitution of the Republic\; The purpose of this investigation is to know if said institution monitors the protection measures they have issued. Through the application of research techniques, the opinion of legal professionals who have knowledge on childhood and adolescence issues was known, as well as the procedures for issuing protection measures that benefit minors\; In addition, the main members of the Cantonal Board of Ibarra were also interviewed. In the present work it was concluded that the protection measures issued in 2018 by the cantonal rights board of Ibarra are not one hundred percent effective, because there is no compliance by the people on whom they fall these measures, and it was also established that it does not have enough personnel to follow up on the cases in which said measures were issued.